Peran Petugas Pemasyarakatan dalam Penegakan Hukum terhadap Warga Binaan: Studi Kasus pada Lembaga Pemasyarakatan Kelas 2 Parepare - Haskari, Haskari; Muzakkir, Abd. Kahar (Sovereign: International Journal of Law, 2024)
This study aims to examine the role of officers at Parepare Class 2 Correctional Institution in law enforcement towards inmates, as well as the factors influencing that role. This research utilizes an empirical legal research approach. Data collection was conducted using three methods: questionnaires, interviews, and observation. The research sample, consisting of 35 individuals, was determined using saturated sampling and proportionate stratified sampling techniques. The collected data were assessed for validity and subsequently analyzed qualitatively. The findings show that the role of officers at Parepare Class 2 Correctional Institution in law enforcement towards inmates is adequate. This is evidenced by the alignment of key indicators with the collected data, such as in religious guidance and skills training for inmates. Several factors influence the role of correctional officers, including officer integrity, facilities and infrastructure, and inmate awareness. These three factors significantly affect the role of correctional officers in implementing rehabilitation programs for inmates at Parepare Class 2 Correctional Institution. It is recommended that correctional officers receive training to enhance their professional development, leading to improved inmate rehabilitation. Furthermore, it is suggested that the Head of Parepare Class 2 Correctional Institution enhance facilities and infrastructure and establish more cooperation with government agencies and Small and Medium Enterprises (SMEs) to improve inmate skills at Parepare Class 2 Correctional Institution.